DEVELOPMENT AND DISTRIBUTION OF THE BRACHIAL PLEXUS IN BLUE-FRONTED PARROT (Amazona aestiva, Linnaeus, 1758 - Rayssa Marley Nóbrega da Silva; Paula de Oliveira Figueiredo; Marcelo Ismar Santana (Ciência Animal Brasileira, 2015)
Local anesthetic procedures are commonly used in domestic and wild birds, because of its low cost and fast induction, as long as applied with great precision, which requires specific anatomical knowledge of the site of incision. This study aimed to establish the origin and distribution of the brachial plexus of the Blue-fronted Parrot (Amazona aestiva) by anatomic dissection of the skin and musculature of 22 specimens (17 males and 5 females) from the Wild Animals Screening Center of the Federal District after death by natural causes. The dissection work promoted the isolation of the forming roots of the brachial plexus, as well as its ramifications. The brachial plexus was formed by four trunks, including the ventral spinal cord rami segments from C9 to C10, C10 to C11, C11 to T1 and T1 to T2, which joined into a short common trunk, branched into dorsal and ventral cords. The thin nerves subcoracoideus and subscapularis and the branch to the scapulohumeralis muscle originated from the common trunk. The dorsal cord originated the anconeal, axillaris and radialis nerves, while the ventral cord gave origin for the pectoralis cranialis, pectoralis caudalis, coracobrachialis and medianoulnaris. These branches innervated the muscles of the extensor and flexor compartments of the forelimb, pectoral muscles and overlying skin.